A GRAMMATICAL INTERFERENCE FROM INDONESIAN INTO ENGLISH TRANSLATION - Sari, Hilda Mutia; ., H. Sudarsono; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: This research aims to investigate the type and the frequency of grammatical interference of Indonesian into English translation. This research is descriptive. The tool of data collecting is a written test. The participants are 12 students selected randomly.The research findings show that the research subject made grammatical interference of their Indonesian into English translation. The interference is classified into four types namely, interference of addition, ommision, disordering and misinformation. There are two factors that cause interference in translation including interlingual and intralingual. The inter -lingual errors include the interference of Indonesian rules and the intra - lingual includes the application of rules in the target language, overgeneralization, an ignorance of rule restriction and false concept of hypothesis. Keywords : Grammatical, Interference, Indonesian, English and Translation. Abstrak:Tujuan dari  penelitian ini adalah untuk mengetahui jenis jenis kesalahan dan frekuensi dari kesalahan gramatikal terjemahan Bahasa Indonesia kedalam Bahasa inggris. Penelitian ini adalah penelitian deskriptif. Alat untuk mengumpulkan data adalah tes tertulis. 12 partisipan terpilih secara acak dalam penelitian ini. Hasil dari penelitian ini menunjukan bahwa subjek penelitian membuat kesalahan gramatikal dalam terjemahan bahasa Indonesian ke dalam Bahasa inggris. Kesalahan itu diklasifikasi kedalam 4 jenis yaitu kesalahan dalam penambahan, kesalahan pengurangan, kesalahan penyusunan dan kesalahan penggunaan dalam terjemahan. Ada 2 faktor yang menyebabkan kesalahan dalam penerjemahan yaitu interlingual dan intralingual. Inter lingual termasuk kesalahan dalam aturan Bahasa Indonesia dan intra lingual dalam penggunaan target Bahasa, overgeneralisasi, pengabaianaturan dan pemahaman yang salah terhadap hipotesis. Kata Kunci:Gramatikal, kesalahan, Bahasa Indonesia, Bahasa Inggris, dan terjemahan